2016
DOI: 10.9745/ghsp-d-16-00084
|View full text |Cite
|
Sign up to set email alerts
|

Vouchers: A Hot Ticket for Reaching the Poor and Other Special Groups With Voluntary Family Planning Services

Abstract: Vouchers can be a highly effective tool to increase access to and use of family planning and reproductive health services, especially for special populations including the poor, youth, and postpartum women. Voucher programs need to include social and behavior change communication with clients and quality assurance for providers, whether in the private or public sector. In the longer term, voucher programs can strengthen health systems capacity and provide a pathway to strategic purchasing such as insurance or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…Lastly, studies could contribute in testing and documenting effective strategies that convert vouchers to government-financed models that can sustain the approach beyond donor horizons (Menotti and Farrell 2016).…”
Section: Future Researchmentioning
confidence: 99%
“…Lastly, studies could contribute in testing and documenting effective strategies that convert vouchers to government-financed models that can sustain the approach beyond donor horizons (Menotti and Farrell 2016).…”
Section: Future Researchmentioning
confidence: 99%
“…Menotti and Farrell note that “voucher programs may strengthen capacity and readiness in the health system for implementing universal health coverage.” 1 We concur. This readiness can only come from dialogue that spans far wider than the implementers of the voucher program and its direct donors.…”
Section: Reorientating Voucher Programs To Catalyze Health Financing mentioning
confidence: 72%
“…We found the commentary on vouchers by Menotti and Farrell, published in the September issue of GHSP, 1 thought-provoking and comprehensive. At Marie Stopes International (MSI), every year we deliver half a million voluntary contraception and maternal health services via voucher programs in 8 countries.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Voucher programs have been of increasing interest to policy makers and reproductive health care consumers in LMICs. 20 24 A recent systematic review found that family planning voucher programs were associated with improved contraceptive uptake, reduced fertility, and increased family planning coverage among low-income populations. However, research gaps were noted, including a lack of study outcomes on family planning quality, unintended outcomes, client qualitative experiences, family planning voucher integration with health systems, and issues related to scale-up of the voucher approach.…”
Section: Introductionmentioning
confidence: 99%